Speculation and Praxis : Jahrbücher für speculative Philosophie and the Actualization of Philosophy - Kallio, Lauri (Uniwersytet Mikołaja Kopernika, 2025)
The paper addresses the journal Jahrbücher für speculative Philosophie, published between 1846 and 1848 in Darmstadt. The paper focuses on the forewords of the journal written by the sole editor Ludwig Noack (1819-1885). In these forewords, Noack elaborates the current situation of philosophy. He outlines his vision for the future philosophy. It would be meaningful not only for professional philosophers but also for the general audience. Moreover, it would be closely associated with other sciences. Noack’s vision was inspired by August Cieszkowski’s (1814-1894) socalled “Philosophie der Tat” (the philosophy of action), which resonated with the entire generation of German Hegelians 仕om the late 1830s. Noack realized his journal in co-operation with the “Philosophische Gesellschaft zu Berlin”, founded by Cieszkowski and Georg Wilhelm Friedrich Hegel’s (1770-1831) former student Carl Ludwig Michelet (1801-1893) in 1843. © 2024, Nicolaus Copernicus University. All rights reserved.